Contribution Analysis: An approach to exploring cause and effect - Mayne, J. (ILAC, 2008)
Questions of cause and effect are critical to assessing the performanc e of programmes and projects. When it is not practical to design an ex periment to assess performance, contribution analysis can provide cred ible assessments of cause and effect. Verifying the theory of change t hat the programme is based on, and paying attention to other factors t hat may influence the outcomes, provides reasonable evidence about the contribution being made by the programme.